(untitled) (Global Journal of Management and Business Research, 2021)
To study the situation and influencing factors of Chinese rural labor force working abroad is not only conducive to relieving the employment pressure of China’s labor market, but also conducive to adjusting the domestic economic structure and laying the foundation for China’s "going out" strategy. The researchers focus on the survey data of the rural labor force of Shandong Labor Cooperation Company. Firstly, we make statistical analysis on the individual characteristics and the situation of migrant workers. Secondly, through the interactive analysis of the individual characteristics of rural labor force and the situation working abroad, it is found that there are differences in the length of time going abroad, the country of work, the place of work, the type of work, the income and the willingness to return to Japan and South Korea of Shandong Province with different gender, age, native place and education level. Thirdly, we construct OLS regression model to analyze the influencing factors of rural labor force’s income. Finally, based on the research findings, we put forward some policy suggestions to promote the labor force to work abroad.